Changing trends in diagnosis, staging, treatment and survival in lung cancer: comparison of three consecutive cohorts in an Australian lung cancer centre. Issue 8 (August 2016) - Denton, E. J.; Hart, D.; Wainer, Z.; Wright, G.; Russell, P. A.; Conron, M.
Abstract : Background: Lung cancer accounts for significant morbidity and mortality worldwide. The effect of recent changes in demographics and management on outcomes in Australia has not been clearly defined. Aims: To compare three consecutive lung cancer cohorts to evaluate emergent differences in diagnosis, management and mortality. Methods: For comparative analysis, 2119 lung cancer patients were divided into three successive cohorts. Current death data were sought from the Victorian Cancer Registry. Results: Age at diagnosis, mode of presentation and pathology did not significantly differ between the groups. Significantly more females were diagnosed with lung cancer in the most recent cohort ( P = 0.04). Amongst non‐small‐cell lung cancer patients, there were more adenocarcinomas and less large cell carcinomas in the latest cohort ( P = <0.01). More patients from the most recent cohort were staged pathologically and via positron emission tomography and fewer were clinically staged ( P = <0.01). The most recent cohort had a greater proportion of Stage IV disease ( P = <0.01) and more curative surgical or combined modality radiotherapy and chemotherapy versus palliative radiotherapy or supportive care ( P = <0.01). Overall 5‐year survival improved significantly in the most recent cohort, even after adjustment for age, gender and stage ( P = <0.01). Conclusion: Comparison of three lung cancer patient cohorts diagnosed between 2001 and 2013 highlights emergent changes in lung cancer demographics, management and outcomes. These include recent increases in proportion of females, pathological and positron emission tomography staging, and Stage IV disease, as well as improved survival despite later stage disease.